PERAN AKUN INSTAGRAM @dr.tirta SEBAGAI INFLUENCER DALAM EDUKASI PENCEGAHAN COVID-19 DI MEDIA SOSIAL INSTAGRAM: ANALISIS ISI KONTEN INSTAGRAM @dr.tirta - Agustian Galih Lisanto; Saifuddin Zuhri; Dyva Claretta; Catur Suratnoaji (Linimasa : Jurnal Ilmu Komunikasi, 2023)
In the current COVID-19 pandemic, social media and its influencers have a big role in disseminating information. As an influencer, @dr.tirta uses it to educate on COVID-19 prevention through the content he creates. Informal education through social media that occurs on the basis of a sense of care and responsibility to followers on Instagram. This study uses a qualitative content analysis method according to Holsti. This study aims to look at the content about COVID-19 education uploaded to the @dr.tirta Instagram account about COVID-19 prevention education. The results in this study indicate that the COVID-19 prevention education content created by the @dr.tirta account has two categories, namely the COVID-19 information category and vaccine information. Uploading content with @dr.tirta's direct and firm style of delivery is one of the factors for the @dr.tirta account to become one of the most noticed influencers during the pandemic era. The content created is easier because @dr.tirta also uses common language that is easily accessible to ordinary people.